LANGUAGE DIDACTIC PRINCIPLES OF CULTURE FORMATION OF PEDAGOGICAL COMMUNICATION OF FUTURE TEACHERS PRIMARY CLASSES - I.V. Onyshchenko (Academy of Cognitive and Natural Sciences, 2010)
In article features of formation of culture of pedagogical dialogue of the future teachers of elementary grades are considered; is professional - communicative abilities of the future teachers are defined and described.